Novel system of grading system of grading fresh fruit bunches (FFB) of oil palm fruit / Azli Abd Razak, Shahril Kushairi and Nor Hayati Saad - Abd Razak, Azli; Kushairi, Shahril; Saad, Nor Hayati (2007)
This research concerns about the analysis pertaining the relation between forces (injection) with the ripeness level of palm oil fruit depending on two different fields where the FFB are being harvested. The injection force from the samples were taken by a digital force gauge that can measures compression forces with a customized tool tip that is designed solely for injecting the fruitlets of an FFB. The ripeness levels of the sample will first being determined by the previous grading standard before the measurement can be initiated. This study revealed that there is positive correlation between injection forces with the ripeness level of FFB. The useful of the study can be used in the future to improve the efficiency of grading of oil palm fresh fruit bunches (FFB).